The Effect of Habbatussauda (Nigella sativa) on TNF-α and IL-6 Levels in Wistar Rats Induced High Fat Diet - Yenyen Sulistio Iriana Karyani; Agung Putra; Titiek Sumarawati (Gema Lingkungan Kesehatan, 2024)
Habbatussauda (Nigella sativa) contains the active substance thymoquinone which has antihypercholesterolemic, antioxidant, and anti-inflammatory effects. Administration of Habbatussauda oil can improve TNF-α and IL-6 levels in hypercholesterolemia conditions. The research aimed to determine the effect of giving habbatussauda on levels of TNF-α and IL-6 in rat fed a high-fat diet. Post-test-only control group design experimental research for 45 days. A sample of 30 Wistar rats aged 8 weeks, weighing 150-200 grams and adapted for 7 days, were randomly divided into 5 groups, namely: normal control group (K1), negative control group given a high-fat diet (K2), treatment group given habbatussauda 0.001 mL/gBB (K3), treatment group given habbatussauda 0.002 mL/gBB (K4), treatment group given habbatussauda 0.004 mL/gBB (K5) treatment was given for the last 2 weeks. TNF-α and IL-6 levels were measured by the ELISA method. Data were analyzed using One Way Anova then continued with the Post Hoc LSD. The mean ± SD of TNF-α levels in groups K1, K2, K3, K4 and K5 were 83.36 ± 23.73, 246.47 ± 43.21, 155.83 ± 36.38, 171.80 ± 22.50, and 195.77 ± 47.67 pg/mL, respectively. In IL-6 groups K1, K2, K3, K4 and K5 were 33.83 ± 8.55, 115.11 ± 16.51, 58.85 ± 19.71, 76.70 ± 6.03, and 78.05 ± 17.33 pg/mL, respectively. One Way Anova test for TNF-α and IL-6 levels showed significant differences between groups (p = 0.000 and p = 0.000). In the post hoc test, TNF-α and IL-6 levels in K3, K4, and K5 were significantly lower than in K2 (p = 0.000). Administration of Habbatussauda can reduce TNF-α and IL-6 levels in rat induced by a high-fat diet.